THE ATTRIBUTES OF ECOMMERCE TOWARDS PURCHASE INTENTION: A CONCEPTUAL PAPER - Nor Amira Mohd Ali; Muhammad Hanif Abdul Gafar (International Journal of Accounting, Finance and Business, 2023)
The impact of internet technologies on the global market is undeniable. With saturated eCommerce platforms, most of the business owners compete in selling their products online. This scenario has gotten tougher and tougher because the possibilities of getting their products purchased by consumers over other companies are darn right difficult. This is due to the Malaysia is one of the countries which involved with eCommerce since year 2004 (eBay Malaysia) and within few years followed by two major players (Lazada and Zalora) in 2012. By 2015, Shopee was launched and has grown tremendously which attracts approximately 55 million visitors per month. Indirectly, making it the most visited eCommerce platform in the country. Thus, business owners must have a leg up in structuring and designing their business online through the eCommerce platforms. Previously, the analogy for this could be made by (consumers) getting into physical store which have poor presentation and visualization of the products will make the consumers leave that store. The same concept will be implemented on an eCommerce platform. As a business owner, they should think of their customer on how they will be affected by the eCommerce website. Therefore, this study will examine what are the attributes of eCommerce which lead to the consumer’s purchase intention and to measure the effectiveness of these attributes towards purchase intention. By using a suitable sampling technique, the data will be collected from the distribution of questionnaires to the respondents.